Structural subclass of place-labelled petri net controlled grammars: State machine - Mohamad Jan, Nurhidaya; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (UTM, 2016)
A place-labelled Petri net controlled grammar is, in general, a context-free grammar equipped with a Petri net and a function which maps places of the net to productions of the grammar. The languages of place-labelled Petri net controlled grammar consist of all terminal strings that can be obtained by parallel application of the rules of multisets which are the images of the sets of input places in a successful occurrence sequence of the Petri net. In this paper, we investigate the structural subclasses of place-labelled Petri net controlled grammar which focus on the state machine. We also establish the generative capacity of state machine of place-labelled Petri net controlled grammars.